2006
DOI: 10.1093/gerona/61.1.78
|View full text |Cite
|
Sign up to set email alerts
|

Power Training Improves Balance in Healthy Older Adults

Abstract: Power training improves balance, particularly using a low load, high velocity regimen, in older adults with initial lower muscle power and slower contraction. Further studies are warranted to define the mechanisms underlying this adaptation, as well as the optimum power training intensity for a range of physiological and clinical outcomes in older adults with varying levels of health status and functional independence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
178
1
14

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 268 publications
(205 citation statements)
references
References 25 publications
4
178
1
14
Order By: Relevance
“…A study demonstrated that older people (~72 years of age) with similar muscle mass to that of younger people (~22 years of age) covered a shorter distance in the 6 min walk test 34. Studies have shown that older people who fall have less muscle power in the lower limbs compared with their non‐faller counterparts,10, 35 suggesting that muscle power is a determinant of fall risk.…”
Section: Discussionmentioning
confidence: 99%
“…A study demonstrated that older people (~72 years of age) with similar muscle mass to that of younger people (~22 years of age) covered a shorter distance in the 6 min walk test 34. Studies have shown that older people who fall have less muscle power in the lower limbs compared with their non‐faller counterparts,10, 35 suggesting that muscle power is a determinant of fall risk.…”
Section: Discussionmentioning
confidence: 99%
“…The Borg Scale (25) was used to assist in evaluating when 1RM was reached. Peak muscle power was obtained at 40%, 50%, 60%, 70%, 80%, and 90% of the 1RM approximately 30 minutes after 1RM testing (26,27). Participants were instructed to exert "as fast as possible" at each relative percentage of the 1RM.…”
Section: Methodsmentioning
confidence: 99%
“…The inclusion of explosive contractions in strength training results in overall neuromuscular adaptations in the elderly, such as increases in the maximal concentric power, the rates of force development and rapid muscle activation, and maximal dynamic strength (Häkkinen et al 2001;Izquierdo et al 2001a). Moreover, certain studies have reported that strength training using high velocity during concentric contractions results in greater improvements in functional capacity when compared with strength training using only slow velocity of contractions (Earles et al 2001;Sayers et al 2003;Henwood et al 2008;Miszko et al 2003;Orr et al 2006;Bottaro et al 2007;Correa et al 2012;Pereira et al 2012;Reid and Fielding 2012). In the study by Pereira et al (2012), 12 weeks of high-speed power training improved walking speed and performance on functional tests, such as "sit to stand" and "get up and go" in elderly women.…”
Section: Long-term Concurrent Training Programsmentioning
confidence: 99%